Histomorphometric Study of the Proportion of Cortex and Medulla of the Adrenal Gland-A Postmortem Study (Mediscope, 2021)
Background: The human adrenal gland shows a distinct proportion of two histological zones, named the cortex and the medulla, from outer inwards, in its histological appearance with differences in its cellular components and functions.Objective: The present study aims to see the variation in the proportion of the cortex and the medulla of the adrenal glands with age in a Bangladeshi population.Methods: A cross-sectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2008 to June 2009, based on collection of 140 postmortem human adrenal glands from 70 unclaimed dead bodies, in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into four age-groups including A (11-20 years), B (21-30 years), C (31-40 years) & D (41-60 years). Histological slides were prepared by using routine haematoxylin and eosin stain (H & E). Five best prepared slides from each group were examined under light compound microscope with low magnification. The thickness of adrenal cortex and medulla were measured by using ocular and stage micrometer and then converted into percentage volume.Results: The mean volume of the right adrenal cortex were found 83.64±3.71% in group A, 83.90±1.75% in group B, 83.74±5.78% in group C, 84.80±3.82% in group D, while the mean volume of the corresponding medulla were found 18.16±3.23% in group A, 15.70±2.71% in group B, 16.26±3.97% in group C, 16.20±4.04% in group D. The mean volume of the left adrenal cortex were found 84.64±3.49%, 84.90±1.75%, 84.20±3.40%, 85.44±2.66% in group A, B, C and D respectively, while the mean volume of the corresponding medulla were found 17.26±3.84%, 17.00±2.37%, 16.00±3.20% and 14.36±2.33% in group A, B, C and D respectively. The differences among the groups were not statistically significant.Conclusion: No difference was found in the proportion of the cortex and the medulla of adrenal gland in different age-groups.Mediscope Vol. 8, No. 1: January 2021, Page 1-6